Watching polymers grow: real time monitoring of polymerizations via an on-line ESI-MS/microreactor coupling - Haven, Joris J.; Vandenbergh, Joke; Junkers, Tanja (Chemical communications (Cambridge, England), 2015)
A technique for the continuous on-line monitoring of polymerization processes by electrospray ionization mass spectrometry (ESI-MS) is presented via coupling with a commercial microreactor system. The potential is demonstrated by monitoring polymerizations in real time under synthesis conditions. Furthermore, a single acrylate monomer insertion into a oligo-RAFT agent, as used in the synthesis of mono-disperse sequence controlled materials, was optimized by on-line screening of reaction conditions.